Advances in Polymer Nanocomposites for Efficient Photocatalytic Dye Degradation: Synthesis, Mechanisms, and Environmental Applications - Pandit, Vikram Uttam (Biopolymer Applications Journal, 2026)
<audio class="audio-for-speech"></audio> Translator <audio class="audio-for-speech"></audio> Translator The discharge of synthetic dyes from various industrial activities poses a severe environmental threat due to their high stability, toxicity, and resistance to biodegradation. Polymer nanocomposites, which integrate functional polymers with semiconductor nanoparticles, have emerged as promising materials for the photocatalytic degradation of organic dyes under ultraviolet and visible light irradiation. This review comprehensively examines recent progress in the development of polymer nanocomposite photocatalysts, focusing on their synthesis methodologies, structural attributes, and underlying degradation mechanisms. The synergistic interactions within these hybrid systems facilitate improved charge separation, extended light absorption, and enhanced dye adsorption, leading to superior photocatalytic performance. Various classes of polymer nanocomposites, including polymer–metal oxide, conducting polymer-based, biopolymer-based, and hybrid composites, are discussed with respect to their functional roles in dye degradation and wastewater remediation. Furthermore, the review addresses recyclability, long-term stability, and practical applicability in real effluent systems. Future perspectives emphasize the advancement of green, biodegradable, and multifunctional polymer nanocomposites with enhanced durability, scalability, and environmental compatibility for sustainable wastewater treatment processes.